Efficacy of wechat instant messaging platform for peer feedback on undergraduate students‟ english academic writing performance: a systematic literature review - Shi, Sun; Razali, Abu Bakar; Ab Jalil, Habibah; Ismail, Lilliati (Sciedu Press, 2024)
Peer feedback has become a crucial element in the field of English as a second/foreign language (ESL/EFL) writing. There has been a notable scholarly interest in the integration of peer feedback in English writing instruction. Among Chinese undergraduate students, there is a growing tendency to use instant messaging systems, such as WeChat, for peer feedback. WeChat distinguishes itself from other platforms by its extensive usage in China, particularly owing to its user-friendly features. However, there is a lack of systematic research in the current literature to explore the effectiveness of using WeChat for peer feedback in English writing. In particular, there is a lack of research on five aspects of students‟ English writing performance when using WeChat as a platform for peer feedback, such as content and idea, coherence and cohesion, grammar and form, word choice and vocabulary, and organization and structure. This article aims to provide an overview of the investigation of the effectiveness of using WeChat as an instant messaging platform through a literature review. The authors adhered to predetermined criteria for what literature were included and excluded. Ultimately, the authors reviewed a collection of 30 research articles from the year 2011 to 2023 that are directly related to the topic at hand. This review encompasses an evaluation of the research designs, findings, discussions, and gaps in research identified in these articles. This review offers a comprehensive comprehension of the present status of research in this field. Moreover, it emphasizes the need for additional academic investigation, specifically targeting the task of filling the recognized gaps in knowledge. Furthermore, the conclusion highlights the necessity of further studies, which needs to explore the long-term effects of incorporating WeChat and peer feedback on enhancing students‟ writing performance. This encompasses various aspects, such as content and idea, coherence and cohesion, word choice and vocabulary, organization and structure, as well as grammar and form.